TRENDS IN THE FISH MARKET AND FISHING INDUSTRY PRODUCT DEVELOPMENT - Lebid, Iryna; Anufriyeva, Tetyana (Proceedings of National Aviation University (archive), 2019)
The purpose of the article is to study the trends in the fish market and fish industry product development, to analyze the exports and imports of fish products to Ukraine to further develop cold supply chains. The paper gives a comprehensive analysis of fish and aquaculture production in the world. It has been identified that leaders in fish capture are Asian countries, while about 80% of the total fish production is provided by only 20 countries, among which China is an undisputed leader. Besides, the global fish and seafood supply in the market for a long time has been generated by Peru, the USA, Chile, Indonesia, Japan, India, the Russian Federation, Thailand, Norway, Latvia, and Estonia. It is figured out that the main countries importing fish and fish products to Ukraine are Ireland and Norway, the ratio of imports to exports of fish and fish products in Ukraine are 2% to 98%, despite the fact that Ukraine has access to the sea, capture levels and exports are very small. It is also considered the main importing countries of fish and fish products to Ukraine. It is estimated that 90% of all imported products are frozen, and their transportation from the countries of the European Union is carried out by automobile transport. The article enables to conclude that the Ukrainian fish market is import-dependent and has a seasonal nature. The article focuses on the need to take into account transportation geography to form the technological process of fish delivery.